2008
DOI: 10.1203/pdr.0b013e318181b3b2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary NGAL in Premature Infants

Abstract: Premature infants are at unique risk for developing acute kidney injury (AKI) due to incomplete nephrogenesis, early exposure to nephrotoxic medications, and coexisting conditions such as patent ductus arteriosus (PDA) and respiratory distress syndrome (RDS). Unfortunately, laboratory testing for the diagnosis of AKI in this population is problematic because of the physiology of both the placenta and the extra-uterine premature kidney. Recent research has led to the development of promising biomarkers for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
105
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 22 publications
16
105
1
1
Order By: Relevance
“…In line with previous studies 8,9 we found in univariate analyses a negative association between BW and GA, and uNGAL, but not sNGAL. This finding has been confirmed by multiple regression models on the first and second week of life, but not a month after birth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous studies 8,9 we found in univariate analyses a negative association between BW and GA, and uNGAL, but not sNGAL. This finding has been confirmed by multiple regression models on the first and second week of life, but not a month after birth.…”
Section: Discussionsupporting
confidence: 93%
“…6,7 Few studies have analyzed total sNGAL and uNGAL levels in preterm newborns. Huynh et al 8 revealed that uNGAL levels are declining with gestational age (GA) by 17.8% by each week in very low birth weight infants (VLBW) with birth weight (BW) ranges from 790 to 1490 g. Similar results were obtained by Lavery et al 9 who showed uNGAL to be inversely related to BW and GA in 20 infants with BW range from 500 to 1500 g. Contradictory data has also been published. Inoue et al 10 reported a strong positive correlation between GA and sNGAL in 52 infants (mostly preterm) at birth, admitted to a tertiary neonatal intensive care unit (NICU).…”
Section: Introductionmentioning
confidence: 60%
“…131 Identification and validation of biomarkers would allow earlier detection of AKI in premature infants and permit generalizability between single-center studies. [132][133][134] Biomarkers including urine cystatin C, uromodulin, epithelial growth factor, neutrophil gelatinase-associated lipocalin, and osteopontin predict AKI in specific neonatal populations. 135,136 …”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…We speculate that in this study greater care may have been taken in collecting specimens to be used for urine culture than in the prior study, in which urine was not usually cultured. Third, GA and AKI (30)(31)(32) have been associated with changes in UNGAL concentrations in infants, independent of infection. Regression models controlling for the effects of GA, sex, and AKI found no significant interactions between these covariates and culture results; however, our study was neither designed nor powered to detect such effects.…”
Section: Limitationsmentioning
confidence: 99%